Electrochemical Properties Of Lithium-Ion Battery Under Elevated Temperature - Kulíková, Barbora (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2019)
This article presents a topic of the elevated temperature influence on lithium-ion accumulators. The theoretical part of the paper focuses on the basic principles of lithium-ion batteries, their advantages and influence of the temperature on their functionality. The experimental part deals with three different experiments comparing measured and manufacturers’ parameters, and examining the influence of the temperature and current on a capacity along with charging and discharging characteristics.
Keywords: Accumulators; lithium-ion batteries; capacity; temperature; charging characteristics; discharging characteristics